2013
DOI: 10.1055/s-0032-1333278
|View full text |Cite
|
Sign up to set email alerts
|

Comparison Between NSAID and Intra-articular Corticosteroid Injection in Frozen Shoulder of Diabetic Patients; a Randomized Clinical Trial

Abstract: Introduction: Frozen shoulder or adhesive capsulitis is a relatively common encountered musculo-skeletal disease in which arouses following soft tissue involvement of glenohumeral joint and presents with pain and limitation of shoulder? active and passive motions. The incidence of frozen shoulder among diabetic patients is about 10?20%, stiffness in such patients is more severe and should be managed actively. Local Glucocorticoid injection, NSAIDs and physiotherapy each can relief the symptoms. The aim of this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
47
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(48 citation statements)
references
References 4 publications
0
47
0
1
Order By: Relevance
“…The fulltext manuscripts of the 16 studies were retrieved and reviewed. Of these, ten studies (8,9,(15)(16)(17)(18)(19)(20)(21)(22) met the criteria for inclusion in the review. Six studies were excluded -fi ve due to poor quality (Jadad score ≤ 2) (23)(24)(25)(26)(27) and one due to its participants' symptoms not being specifi c to adhesive capsulitis.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The fulltext manuscripts of the 16 studies were retrieved and reviewed. Of these, ten studies (8,9,(15)(16)(17)(18)(19)(20)(21)(22) met the criteria for inclusion in the review. Six studies were excluded -fi ve due to poor quality (Jadad score ≤ 2) (23)(24)(25)(26)(27) and one due to its participants' symptoms not being specifi c to adhesive capsulitis.…”
Section: Resultsmentioning
confidence: 99%
“…(9) The mean pretreatment duration of symptoms in selected studies ranged from 12.2 weeks (16) to eight months. (20) Only two studies reported the stage of adhesive capsulitis of the participants: the freezing and frozen stages in Roh et al (8) and freezing stage in Yoon et al (9) Seven of the studies were conducted in outpatient settings, (9,(15)(16)(17)(18)(19)(20) of which one was conducted in general practice. (18) There were differences in the inclusion criteria of the studies, particularly in the degree of loss of active and passive ROM.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…If not, were patients with diabetes mellitus equally distributed among the treatment groups? This is relevant information, because diabetes mellitus is associated with a more protracted course with less response to conservative treatment [3].…”
mentioning
confidence: 99%